(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
This article deals with the construction and study of exact schemes, as well as their corresponding truncated schemes of the "m" rank for the marginal problem in the case of a system of ordinary second-order differential equations with degeneration